Politicized Transnationalism: The Visegrád Countries in the Refugee Crisis - Koß, Michael (2020)
Existing research on the evolution of European integration has pitted economic against identity issues. In the economic sphere, governments are arguably able to pursue their preferences more independently. If, however, identity issues become politicized this is supposed to suggest that governments lose their dominant position in integration and gradually become agents of Eurosceptic parties and/or electorates. This article looks at a phenomenon neither the intergovernmentalist nor the postfunctionalist perspective can fully explain: the emergence of the Visegrád Group (V4) as a collective actor in European politics in early 2016. This emergence occurred in the wake of the refugee crisis during which the identity issue of migration was politicized. However, there was no coherent partisan composition uniting V4 governments. Based on a sequence elaboration of all press statements of meetings of the V4 Prime Ministers since their EU-accession in 2004, we show that what at first sight appears to be informed by anti-immigrant and Eurosceptic sentiments may in fact display a more ambivalent position towards regional integration. The post-refugee crisis V4 appears as a case of politicized transnationalism—that is, cooperation to achieve transnational interests under the condition of politicization. This transnational interest not only comprised opposition to a relocation of migrants, but also the maintenance of a core transnational freedom within the EU, namely free movement under the Schengen acquis. We conclude that, under the condition of increasing politicization, identity issues help to forge government alliances of governments pursuing economic preferences.